341 Phase 1b/2 study of BXCL701, an oral activator of the systemic innate immunity pathway, combined with pembrolizumab (pembro), in men with metastatic castration-resistant prostate cancer (mCRPC). (9th November 2020) - Aggarwal, Rahul; Costin, Dan; Zhang, Jingsong; Monk, Paul; Linch, Mark; Karsh, Lawrence; Healey, Diane; Corsi-Travali, Stefani; Adurthi, Sreenivas; Adedoyin, Adedayo; O'Neill, Vincent
Abstract : Background: BXCL701 (talabostat) is an oral small molecule inhibitor of dipeptidyl peptidases (DPP) primarily DPP8 and DPP9, which triggers inflammasome mediated pyroptosis in macrophages leading to induction of IL-18 and IL-1beta, bridging between innate and adaptive immunity. PD-L1 expression correlates with amplification of DPP8 and DPP9. In syngeneic animal models, significant tumor growth inhibition was observed with BXCL701 plus checkpoint inhibition. In a prior clinical study, single-agent BXCL701 resulted in objective responses in patients (pts) with Stage IV melanoma (unpublished). Methods: In Phase 1b portion of this multicenter study, eligible pts had progressing mCRPC (PCWG3), at least 1 prior systemic therapy, ≤ 2 lines of cytotoxicchemotherapy for mCRPC, no prior anti-PD-1/PD-L1 or other T-cell directed anticancertherapy. Using a 3+3 design, pts received fixed-dose pembro (200 mgIV q21-days) with escalating doses of BXCL701 on days 1–14. The primary endpoint was determination of the recommended Phase 2 dose (RP2D). Response (RECIST 1.1, PSA, CTC), plasma drug concentration and change in relevant immune effector cytokines were also evaluated. Results: 13 pts were treated in 3 cohorts of BXCL701: 0.4 mg qd (n = 3); 0.6 mg qd (n = 3) and 0.6 mg split dose (n=7). 7 pts had adenocarcinoma, 6 had small cell/neuroendocrine prostate cancer features. Prior treatment included ADT (n = 10), 2nd-generation androgen signaling inhibitors (n = 9), chemotherapy (n = 11), RT (n = 11). On-target AEs consistent with cytokine activation were seen at the highest dose levels. In the 0.6 mg qd cohort, all pts had events consistent with cytokine release: 3/3 had hypotension (including 1 grade 3 syncope (DLT)) and 2pts each had dizziness and LE edema. Splitting the 0.6 mg dose improved the tolerability while maintaining the TDD previously associated with objective response; 3/7 pts had fatigue, and 1pt each had low grade hypotension, dyspnea, chills, myalgia. Preliminary anti-tumor activity was seen with 1 pt achieving a PSA response and 3 pts with RECIST1.1 stable disease. BXCL701 was quantifiable in plasma. Consistent dose and time dependent increases in serum IL-18 levels were observed with 0.6 mg split dose. Conclusions: BXCL701 0.3 mg BID (0.6 mg TDD) administered on days 1–14 was identified as the RP2D when administered with pembro 200 mg every 21 days. Splitting the TDD was associated with improved tolerability as evidenced by no reported DLTs and lower rates of other adverse events of interest such as hypotension and peripheral edema. The Phase 2 portion of the study is enrolling. Acknowledgements: All patients, their families, and caregivers who make this study possible; the participating investigators and their staff; Cedric Burg PhD and J. MacDougall PhD of BioXcel Therapeutics, Valery Chatikhine MD of Iqvia Biotech and the Iqvia Biotech team for assisting in the conduct of the study. Trial Registration: NCT03910660EUDRACT 2018-003734-32 Ethics Approval: This study was approved by Institution Review Boards or Ethics Committees affiliated with participating institutions.